The Effect of Crataegus Fruit Pre-Treatment and Preservation Methods on the Extractability of Aroma Compounds during Liqueur Production - Małgorzata Tabaszewska; Dorota Najgebauer-Lejko; Maria Zbylut-Górska (Molecules, 2022)
The leaves, inflorescences, and fruits of hawthorn have long been known for their therapeutic properties. A wide range of hawthorn products, including liqueurs, are manufactured, due to the technological potential of the raw material as well as the richness of its volatile compounds. This study aimed to determine the effect of the liqueur production method and various methods of fruit preservation on the quantitative and qualitative composition of volatile compounds in the liqueurs produced. Hawthorn fruits saturated with sucrose and non-saturated with sucrose, fresh or preserved through one of three methods: freezing, air-drying, and freeze-drying, were used for liqueur preparation. The samples were analyzed using a gas chromatograph–mass spectrometer. They were found to contain 54 volatile compounds classified into 12 groups of chemicals. All 54 identified volatile compounds were detected in the liqueur made from hawthorn fruits non-saturated with sucrose and preserved by freeze-drying. In this liqueur type, 12 of the identified volatile compounds occurred in the highest concentration when compared to the other treatments. Among all volatiles, the following compounds were present in the analyzed liqueurs in the highest concentrations: dodecanoic acid ethyl ester (11.782 g/100 g), lactones (6.954 g/100 g), five monoterpenes (3.18 g/100 g), two aromatic hydrocarbons (1.293 g/100 g), isobensofuran (0.67 g/100 g), alcohol—2-methyl-2-propanol (0.059 g/100 g), and malonic ester (0.055 g/100 g). Among all analyzed liqueurs, the one made from the fruits non-saturated with sucrose and frozen was characterized by the smallest diversity of volatiles, which were present in the lowest concentrations in that liqueur.